Planejamento Participativo nas aulas de Educação Física: uma proposta de intervenção no Ensino Fundamental - Ribeiro, Flavia Ferreira (2020)
The study sought to investigate my pedagogical practice, in a municipal school in Vitória/ES, at EMEF - Maria José Costa Moraes , with students of the 8th years, in 2019. I realized over time that my action it was limited to the contents traditionally de